One-pot Synthesis of 6-Aza-chromone Derivatives Through Cascade Carbonylation-Sonogashira-Cyclization - Gang Cheng (Nature Portfolio, 2017)
Abstract We developed an efficient synthesis of aza-chromones from 3-iodo-4-(1H)-pyridones and terminal acetylenes via a cascade carbonylation-Sonogashira-cyclization reaction. By controlling the use of bases, both 6-aza-chromones 5 and 3-(4-oxo-1,4-dihydroquinoline-3-carbonyl)-4H-pyrano[3,2-c]quinolin-4-ones 6 could be selectively obtained in moderate to good yields.